(untitled) (KYAMC Journal, 2019)
Introduction: Dermatoglyphics is the branch of medical science that is concerned with the study of dermal ridges present on fingers, palms, toes and the soles of the human being. There may have some association between fingerprints and schizophrenia regarding the developmental background of skin ridge pattern and brain.So this study was conducted to find out the fingerprint patterns in schizophrenic patients and also to find out sex variation of fingerprint patterns in between schizophrenic male and schizophrenic female. Objective: This study was carried out with a view to find out the fingerprint patterns in schizophrenic patients. Methodology: A total of 200 samples were selected. Among them, 100 were schizophrenic and 100 were normal healthy control. Samples were taken in between 15 to 40 years of age. Selection of schizophrenic sample was performed by a qualified psychiatrist. Fingerprints were taken by Ink and pad method, described by Cummins. Fingerprint patterns were observed by using a magnifying glass. Results: The frequency of common fingerprint pattern was reduced in schizophrenia. In healthy control loop pattern was predominant. But in schizophrenia frequency of loop pattern was reduced and there was an increased frequency of whorl and arch pattern. Conclusion: Asdermatoglyphics is genetically determined, predominant whorl and arch pattern found among the schizophrenic patients might provide a presumptive value which would aid in diagnosis of the disease. KYAMC Journal Vol. 10, No.-2, July 2019, Page 66-72